PENGARUH MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READINGAND COMPOSITION (CIRC) BERBANTUAN MEDIA BIG BOOK TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SDN PLUMUTAN - Anindita, Deviana; Hawa, Anni Malihatul; Purwanti, Kartika Yuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this research is to determine the effect of the Cooperative Integrated Reading and Composition (CIRC) learning model assisted by Big Book media on the initial reading ability of class I students at SDN Plumutan. This research uses a quantitative approach with a type of experimental method, namely Quasi Experimental Design with a Non-Equivalent Control Group Design design. The population in this study were all students at SDN Plumutan. Meanwhile, the sample in this study were students in class IA and IB at SDN Plumutan. Data collection techniques use cognitive domain tests, observation, questionnaires, interviews and documentation. The data analysis techniques used are the Independent sample T-Test and Simple Linear Regression Test. The results of this research show that: (1) There is a difference in the average beginner reading ability between the control class and the experimental class, which can be seen from the Independent Sample T-Test which shows a sig. 0.001 < 0.05, it can be concluded that there is a significant difference in the average of students' initial reading abilities between the experimental class and control class study groups. (2) There is an influence of the Cooperative Integrated Reading and Composition (CIRC) learning model assisted by big book media on students' beginner reading abilities, this can be seen from the results of the Simple Linear Regression Test which shows a significance of less than 0.05, namely 0.028<0.05 . So the data from the simple linear regression test Summary Model obtained an R. Square value = 0.242 = 24.2%. So it can be concluded that the Cooperative Integrated Reading and Composition (CIRC) learning model assisted by big book media has an effect on the initial reading ability of class I students at SDN Plumutan.   Keywords: big book media, CIRC learning model, beginning reading ability